2016
DOI: 10.1093/jac/dkw166
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in post-operative acute kidney injury following a change in antibiotic prophylaxis policy for orthopaedic surgery: an observational study

Abstract: The use of co-amoxiclav for antibiotic prophylaxis in orthopaedic surgery was associated with a decreased rate of post-operative AKI compared with flucloxacillin and gentamicin and was not associated with increased rates of CDI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Thirty‐six studies were included in the final synthesis: one thesis and 35 journal articles . The 36 studies included 11 randomized controlled studies (two crossover designs), 18 cohort studies, one retrospective survey, three pharmacokinetic and three quasiexperimental studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirty‐six studies were included in the final synthesis: one thesis and 35 journal articles . The 36 studies included 11 randomized controlled studies (two crossover designs), 18 cohort studies, one retrospective survey, three pharmacokinetic and three quasiexperimental studies.…”
Section: Resultsmentioning
confidence: 99%
“…Reported adverse events are summarized in Table . Twenty‐three , of the 36 included studies, reported adverse events in the gentamicin arm of their study although not all adverse events were related to gentamicin. Pons et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations